P1492Comparison of the long-term performance of the quadripolar IS-4 and the bipolar IS-1 left ventricular lead for cardiac resynchronization therapy. (18th June 2020) - Maurhofer, J; Tanner, H; Haeberlin, A; Noti, F; Seiler, J; Baldinger, S H; Roten, L; Lam, A; Asatryan, B; Nozica, N; Franzeck, F; Kueffer, T; et al.
Abstract: BACKGROUND: The implantation of left ventricular (LV) leads for cardiac resynchronization therapy (CRT) and the management of lead-related complications can be challenging. The introduction of the quadripolar IS-4 LV lead may have facilitated the implantation procedure and may have reduced lead-related complications. Data of long-term follow-up (FU) comparing the IS-4 lead with the IS-1 LV lead are rare and conflicting. PURPOSE: Comparison of lead-related complications and all-cause mortality between CRT patients who received an IS-4 or an IS-1 LV lead in the long-term FU. METHODS: Adults with an indication for a CRT-Defibrillator or CRT-Pacemaker, a successful endovascular IS-4 or IS-1 LV lead implantation, and a minimal FU of three years were included in this retrospective study. The combined primary endpoint was freedom from lead-related complications defined as (i) occurrence of persisting high pacing threshold (>2.75V/0.4ms), (ii) unresolved phrenic nerve stimulation, (iii) LV lead dislodgement/disruption, (iv) the necessity of re-interventions affecting the LV lead, and (v) LV lead deactivation/explantation. Secondary endpoints were all singular complications and all-cause mortality. RESULTS: Eligible for the study were 133 patients (IS-4 n = 66; IS-1 n = 67) with a mean FU of 4.03 ± 1.93 years. Baseline characteristics of both patient groups did not differ significantly. Freedom from lead-related complications was higher in patients with an IS-4 lead as compared to an IS-1 lead (Figure 1; 87.9% vs. 65.7%; p = 0.002). The secondary outcomes showed a higher rate of LV lead dislodgement/disruption (4.5% vs. 17.9%; p = 0.015) in the IS-1 patient group and more patients suffered from unresolved phrenic nerve stimulation with an IS-1 lead (3.0% vs. 13.4%; p = 0.029). LV lead deactivation/explantation during FU and LV lead-related re-interventions were fewer in case of an IS-4 lead (4.5% vs 22.4%; p = 0.003; 6.1% vs. 17.9%; p = 0.036, respectively). The rate of persisting high pacing thresholds and all-cause mortality did not differ (4.5% vs. 9.0%; p = 0.492; 22.7% vs 25.4%; p = 0.721, respectively). CONCLUSION: The quadripolar IS-4 LV lead showed in this retrospective study a better long-term performance than the bipolar IS-1 lead.